Citizens and the Corporate Development of the Contemporary Canadian City - Lorimer, James (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1983)
This paper examines the impact of organized citizen groups on the contemporary city in terms of architecture, built form, and planning. Five sections discuss the physical forms of the postwar Canadian city and the basic planning strategies in place at the end of the 1960's; the rise of organized citizen groups and their critique of that set of urban prototypes; the shift in political power that occurred as a result of citizen group activity; the new conditions which came to exist for urban development and planning, and the new city forms that have arisen; and the combination of circumstances which emerged in the early 1980's which put the revised Canadian city on the edge of a serious economic crisis.